2022
DOI: 10.1002/acr.25039
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Race/Ethnicity and COVID‐19 Outcomes in Systemic Lupus Erythematosus Patients From the United States: Data From the COVID‐19 Global Rheumatology Alliance

Abstract: Objective To determine the association between race/ethnicity and COVID‐19 outcomes in individuals with systemic lupus erythematosus (SLE). Methods Individuals with SLE from the US with data entered into the COVID‐19 Global Rheumatology Alliance registry between March 24, 2020 and August 27, 2021 were included. Variables included age, sex, race, and ethnicity (White, Black, Hispanic, other), comorbidities, disease activity, pandemic time period, glucocorticoid dose, antimalarials, and immunosuppressive drug us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…lung disease) or those receiving certain immunomodulatory medications (e.g. rituximab, cyclophosphamide, mycophenolate mofetil) may be at higher risk for worse outcomes [ 1 , 2 ], however these findings are not consistent across studies and have not been replicated in children. Our survey results help to provide additional reassurance to patients with JIIM and their families, demonstrating that no JIIM patients in this cohort reported severe outcomes from COVID-19 and none required hospitalization, including those on numerous immunosuppressive medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lung disease) or those receiving certain immunomodulatory medications (e.g. rituximab, cyclophosphamide, mycophenolate mofetil) may be at higher risk for worse outcomes [ 1 , 2 ], however these findings are not consistent across studies and have not been replicated in children. Our survey results help to provide additional reassurance to patients with JIIM and their families, demonstrating that no JIIM patients in this cohort reported severe outcomes from COVID-19 and none required hospitalization, including those on numerous immunosuppressive medications.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous questions arose surrounding safe access to medical care, community risk reduction to prevent exposure to SARS-CoV-2, and modification of immunosuppressive therapy to decrease the risk of severe complications from COVID-19. Although data are mixed, reports in the literature of patients with adult-onset rheumatic disease suggest that patients with conditions such as systemic lupus erythematosus [ 1 ] as well as those on immunosuppressive therapies, such as rituximab, cyclophosphamide and mycophenolate mofetil, may be at higher risk of poor outcomes [ 2 , 3 ]. To date, there is little evidence to suggest that children with rheumatic disease are at increased risk of more severe outcomes due to COVID-19.…”
mentioning
confidence: 99%
“…In the pre-vaccination era, Bruera et al reported a statistically significant increase in hospitalizations in SLE patients compared with general population (31% vs 17.7%) in Houston, USA, but these numbers obviously do not reflect the reality following vaccine availability [ 82 •]. Hispanic ethnicity and black race were associated with increased hospitalization rate compared to white patients (OR 1.73 and 2.15, respectively] [ 83 ], while increased risk has been associated with the presence of chronic kidney insufficiency (OR 3.51), cardiovascular disease (OR 1.69) and high disease activity (OR 3.94). Moreover, regarding the potential association between various treatments and hospitalization rates, analyses showed that RTX, MMF and cyclophosphamide (CYC) were associated with increased hospitalization rates (with any ventilation or oxygenation, adjusted OR 1.69, 1.36 and 2.55, respectively) [ 80 ].…”
Section: Covid-19 In Patients With Slementioning
confidence: 99%
“…Among patients with rheumatic diseases, these disparities were pervasive across domains including clinical outcomes, access to care and telemedicine, vaccine uptake, and participation in research, in part due to structural barriers but also in part fueled by mistrust (e.g., misinformation about minorities being targeted as “guinea pigs”) (69,74). For example, 2 studies from the Global Rheumatology Alliance registry found that patients with rheumatic disease identifying as Black, Latino, or Asian had more severe COVID‐19 outcomes than those who were White (75,76).…”
Section: Introductionmentioning
confidence: 99%